EFEKTIVITAS STRATEGI PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN KREATIVITAS SISWA - Irfan Rizkiana Raja Nugraha; Supriadi, Udin; Mokh. Iman Firmansyah (Jurnal Penelitian dan Pendidikan IPS, 2023)
Creativity and the ability to think creatively are essential skills of the 21st century. This study aims to obtain a descript ion of the creativity and mathematical creative thinking skills of students after the application of project-based learning. This study uses qualitative research methods to observe participant phenomena in learning activities. Creativity and creative thinking skills are shown by students during the process of planning products, making products, presenting, and evaluating products. The results obtained in this study are students can find out their level of understanding from the work they have made. This can help students to plan to make the next teaching material appropriately. Project assignments carried out in groups can promote creative ideas. This helps students to build confidence in producing innovative work.